MENGUNGKAP MISPERSEPSI SISWA MADRASAH ALIYAH ATAS TUDUHAN NEPOTISME TERHADAP KHALIFAH UTSMAN BIN AFFAN (644-656 M) - Kresna Azhi Fahlevi; Fatiyah Fatiyah (Tanjak: Sejarah dan Peradaban Islam, 2023)
The learning process at the Madrasah Aliyah level which is based on the 2013 Curriculum is carried out using teaching material books provided by the government. One of them is the Student's Book of Islamic History and Culture for Class X Students of Madrasah Aliyah. Unfortunately, in discussing the history of accusations of nepotism against Caliph Uthman bin Affan there are still articles that need further explanation. However, the fact is that this discussion point is often ignored, causing misperceptions among students, even after graduation. This study uses historical research methodologies and library research studies. This study is also part of the study of the history of the Islamic world to complement and dig deeper into the accusations of nepotism leveled against Caliph Uthman bin Affan in the class X MA SKI book which is the background to the emergence of misperceptions among students. Several student books compiled by the Ministry of Religion became the main reference to be later clarified with various other sources such as works by Khalid Muhammad Khalid and other works. Based on the results of the study, Uthman bin Affan did not commit nepotism without certain considerations so that the act of nepotism that he did was considered something that was permissible in Islam. Starting from here, the role of the government, schools and students themselves is very important to prevent the emergence of misunderstandings based on strategies related to textbooks